Influence of the Plaster Physical Structure on Indoor Acoustics - PRĘDKA, Edyta; BRAŃSKI, Adam; WIERZBIŃSKA, Małgorzata (Archives of Acoustics, 2021)
The article presents the main results of research on plaster samples with different physical parameters of their structure. The basic physical parameter taken into account in the research is plaster aeration. Other physical parameters were also considered, but they play a minor part. The acoustic properties of the modified plaster were measured by the sound absorption coefficient; the results were compared with the absorption coefficient of standard plaster. The influence of other physical, mechanical and thermal properties of plaster was not analyzed. The effect of modified plasters on indoor acoustics was also determined. To this end, an acoustic problem with impedance boundary conditions was solved. The results were achieved by the Meshless Method (MLM) and compared with exact results. It was shown that the increase in plaster aeration translated into an increase in the sound absorption coefficient, followed by a slight decrease in the noise level in the room. Numerical calculations confirmed this conclusion.